LEADERSHIP MANAGEMENT STRATEGIES AND ORGANIZATIONAL CHANGE - Yusnita, Reni (Transpublika Publisher, 2022)
This study aims to determine the leadership and change management procedures in an organization. The type of research conducted is a literature study, which aims to collect books and data and other written information related to the discussion of the problem under study. Sources of data from books, magazines and articles. Data collection was carried out using a literature search method using primary legal materials and secondary legal materials. Legal materials will be investigated and analyzed using the approach used in this investigation to answer legal questions in this investigation. The findings reveal that the process of driving change which can begin by taking action to accelerate future change. The process followed by leading the change, drive the change, as well as strike a balance between progression and stability, and raising the level of satisfaction of the staff. Leaders of procedural change are expected to take the initiative when confronted with problems and impediments to promote growth, and have strategies to drive change. To ensure the success of change implementation, the following steps are necessary: 1) setting an annual objective; 2) developing a policy; 3) allocating resources; 4) managing conflicts; 5) establishing an appropriate framework for procedural changes; 6) Find ways to manage people's aversion to change; 7) The establishment of a culture that welcomes and encourages change processes; 8) The nature of the connection between procedural and performance-based rewards; and 9) The role of human resources in the process of putting change procedures into effect.